Coal miner's daughter [videorecording (DVD)] - Apted, Michael; Spacek, Sissy; Jones, Tommy Lee, 1946-; D'Angelo, Beverly; Lynn, Loretta (Universal, 2005)
The story of Loretta Lynn, who rose from the poverty-stricken Appalachian area to become one of the biggest country singers of all time.